2018
DOI: 10.3892/mco.2018.1557
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine supplementation reduces the general fatigue of cancer patients during chemotherapy

Abstract: L-Carnitine (LC) plays an important role in the metabolism of fatty acids, and LC deficiency is associated with a feeling of weakness or general fatigue. Cancer patients receiving chemotherapy often develop LC deficiency, which is considered to be a factor contributing to general fatigue. The aim of the present study was to evaluate the efficacy of LC supplementation as a treatment for general fatigue in cancer patients during chemotherapy. A total of 11 cancer patients who were suffering from general fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The symptoms of these diseases are improved after carnitine supplementation ( 21 ). For cancer patients, the probability of carnitine deficiency has shown to be very high ( 22 ). A research showed that L-carnitine supplementation was safe and might have beneficial effects on fatigue, depressive symptoms and sleep quality in cancer patients ( 23 ).…”
Section: Carnitine and Physiological Functionmentioning
confidence: 99%
“…The symptoms of these diseases are improved after carnitine supplementation ( 21 ). For cancer patients, the probability of carnitine deficiency has shown to be very high ( 22 ). A research showed that L-carnitine supplementation was safe and might have beneficial effects on fatigue, depressive symptoms and sleep quality in cancer patients ( 23 ).…”
Section: Carnitine and Physiological Functionmentioning
confidence: 99%
“…Carnitine supplementation is actively used for the treatment of CFS, fatigue caused by chemotherapy, fatigue in the elderly, and fatigue caused by different neurological diseases [ 19 ]. Supplementation of carnitine is reported to reduce cancer-related fatigue [ 11 , 20 ]. Patients with chronic hepatitis, when treated with l -carnitine along with interferon-gamma and ribavirin also show improvement in fatigue, absenteeism, presenteeism and work-related productivity [ 21 ].…”
Section: -Carnitine and Fatiguementioning
confidence: 99%
“…Suggested mechanisms for fatigue include imbalances in energy production caused by increased energy requirement (e.g., caused by tumor growth, infection, fever, or surgical procedures), reduced availability of substrates (e.g., due to anorexia, nausea, or vomiting), atypical generation of compounds that disrupt metabolic homeostasis or regular functions of muscles (e.g., cytokines and proteolysis inducers), anemia, and hypoxemia. Further proposed processes associate fatigue with the pathophysiology of sleep disturbance and depression [ 11 ]. An animal-model based study showed that treatment of rats with l -carnitine against muscular fatigue reduces free-radical mediated oxidative stress by reducing the production of thiobarbituric acid reactive substances, protein carbonyl, creatine kinase and lipid hydroperoxide [ 26 ].…”
Section: Mechanisms Associated With Fatigue and L -Carnitinementioning
confidence: 99%
See 1 more Smart Citation
“…The most investigated medications among them include psychostimulants, ginseng, corticosteroids, megestrol, mistletoe, guarana, antidepressants specifically selective serotonin receptor reuptake inhibitors (SSRI's). Other agents investigated include Hemopoietin agents [13], Donepezil [14], Testosterone [15,16], Omega 3 polyunsaturated fatty acids [17][18][19], L-carnitine [20][21][22], Astragalus membranaceus [23], Ashwagandha [24], Thyrotropin releasing hormone [25], Microbiome [26], Coenzyme Q10 [27], Micro and macronutrients supplementation such as protein rich diet, vitamin or mineral supplementation [28], and others [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%